1997
DOI: 10.1055/s-2007-979040
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Islets of Langerhans to Pregnancy: β-Cell Growth, Enhanced Insulin Secretion and the Role of Lactogenic Hormones

Abstract: Pregnancy is a unique event in the life span of islet beta-cells. Under the influence of pregnancy islet beta-cells undergo major long term up-regulatory structural and functional changes in response to the increased demand for insulin. Adaptive changes that occur in islets during normal pregnancy include: 1) increased glucose-stimulated insulin secretion with a lowered threshold for glucose-stimulated insulin secretion, 2) increased insulin synthesis, 3) increased beta-cell proliferation and islet volume, 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
428
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(448 citation statements)
references
References 16 publications
11
428
0
9
Order By: Relevance
“…A recent report demonstrated that TCF7L2 is expressed in pancreatic beta cells [13]. Thus, by affecting the WNT signalling, the variant could influence the beta cell proliferation (and hence insulin secretion) that normally takes place during pregnancy [33,35]. The effect size for gestational diabetes mellitus conferred by this variant is similar to that reported in patients with type 2 diabetes [12].…”
Section: Tcf7l2 Rs7903146mentioning
confidence: 55%
See 1 more Smart Citation
“…A recent report demonstrated that TCF7L2 is expressed in pancreatic beta cells [13]. Thus, by affecting the WNT signalling, the variant could influence the beta cell proliferation (and hence insulin secretion) that normally takes place during pregnancy [33,35]. The effect size for gestational diabetes mellitus conferred by this variant is similar to that reported in patients with type 2 diabetes [12].…”
Section: Tcf7l2 Rs7903146mentioning
confidence: 55%
“…During pregnancy beta cells undergo structural and functional changes in response to the increased insulin requirements. These changes include, among others, enhanced glucose-stimulated insulin secretion, increased insulin synthesis and increased beta cell proliferation and islet volume [33]. Genetic factors might therefore predispose to abnormal glucose tolerance during pregnancy by influencing one or more of these physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…1 b-Cell mass depends on the changes in b-cell formation, b-cell volume and b-cell death. The specific contribution of replication to b-cell mass adaptation has been shown in different physiological and experimental conditions, among them normal lifespan, 2 pregnancy, 3 glucose infusion, 4 partial pancreatectomy 5,6 and islet transplantation. 7 Type I diabetes is an autoimmune disease characterized by the destruction of b-cells, and it is believed that proinflammatory cytokines released by activated T cells and macrophages infiltrating the pancreas are important mediators of b-cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, PDX-1 plays a critical role in the development of the pancreas, since mutations in this gene result in pancreatic agenesis in both mice and humans [4,5]. Moreover, studies on the dynamics of the adult pancreas have shown that adult beta cells adjust their mass to distinct metabolic states that occur during the life span, such as pregnancy [6] or obesity [7,8]. The mechanisms involved in this dynamic state shape a delicate balance Diabetes is a major public health problem.…”
mentioning
confidence: 99%